Imaging Characteristics and Endovascular Treatment of Brain Arteriovenous Malformations Mainly Fed by the Posterior Cerebral Artery - Hou, Kun; Li, Chao; Su, Han; Yu, Jinlu (Frontiers in Neurology, 2021)
Background: A BAVM that is mainly supplied by the posterior cerebral artery (PCA) lies deeply in the middle of the bilateral posterior hemispheres. Few studies have investigated the imaging characteristics and endovascular treatment (EVT) of brain arteriovenous malformations (BAVMs) in this area. Methods: A retrospective study was performed for patients who were diagnosed with PCA-BAVMs from January 2015 to December 2019. The PCA-BAVMs were divided into the type I and type II according to their feeding arteries. Type I PCA-BAVMs were supplied by the posterior choroidal artery (PchA) from the PCA. They could be further subdivided into type Ia and type Ib. Type II PCA-BAVMs were supplied by the temporal or occipital branch from the PCA. They could also be further subdivided into the including type IIa and IIb. Targeted embolization of the risk factors was main aim of EVT. Results: Forty-two patients were identified, aging from 6 to 63 years. Twenty-four cases belonged to type I (57.1%, 24/42), including 6 Ia cases and 18 Ib cases. Eighteen cases belonged to type II (42.9%, 18/42), including 7 IIa cases and 11 IIb cases. Immediate complete or nearly complete embolization was achieved in 17 (40.5%, 17/42) cases. Partial embolization was achieved in 25 (59.5%, 25/42) cases. Two (4.8%, 2/42) patients experienced intraoperative or postoperative bleeding. The GOS scores at discharge were 3, 4, and 5 in 2 (4.8%, 2/42), 2 (4.8%, 2/42), and 38 (90.4%, 38/42) cases, respectively. There was no statistical difference between patients in type Ⅰ and Ⅱ groups regarding age, BAVM rupture, SM grade, immediate extent of obliteration, and prognosis. Deep venous drainage was more common in patients of the type I group (p<0.001). Conclusions: Our classification of the PCA-BAVMs was based the segmentation of the PCA, which is a reasonable approach and could guide the strategy of EVT. EVT is a reasonable option for the PCA-BAVMs. The main aim of EVT is securing the weak structures. A targeted EVT aimed at the ruptured part of the BAVM can reduce the risk of early rebleeding.